Akuisisi Bahasa Kedua Secara Alamiah Di Lingkungan Keluarga Bilingual (Analisis Teori Dan Aplikasi) - zainul abidin (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Mastery of a Second Language or Foreign Language can be obtained both guided through the language learning process and naturally through natural acquisition in a language environment such as an environment at home with family, communication with friends or with other people, communication in the market, in the office, or anywhere as well as various other naturally occurring situations. The research aims to describe a second language or a foreign language that is obtained naturally. And the natural model is applied in a family environment or in a bilingual home. This research method is descriptive-analytic qualitative, which is to try to describe the construction of the theory of natural second language acquisition, then critically analyzed, and get the results of the application of natural second language acquisition carried out in a bilingual family environment. The results obtained from this study that a second language has been successfully obtained naturally in a family environment that uses bilingualism in daily communication at home